Microwave-mediated Newman-Kwart rearrangement in water - Hoffmann, Ina; Schatz, Jürgen (RSC Advances, 2016)
For the first time the unimolecular Newman-Kwart rearrangement is performed in pure water. The elevated temperatures required for the 1,3-aryl shift are easily accomplished by microwave irradiation. Differently functionalized substrates underline the expected influence on the reaction rate regarding the electronic and steric effects of the substituents. The utilization of supramolecular additives enables an increase in conversion. Besides, the conduction in a microwave reactor allows for a rapid collection of kinetic data affording the reaction rate constants of the rearrangement of distinct substrates as well as the Arrhenius constant and activation parameters of the conversion of 2- and 4-nitrophenyl-O-thiocarbamate.
Keywords: Green chemistry; physical organic chemistry; water

Organometallic reactions in aqueous phase - Hoffmann, Ina; Schatz, Jürgen (Nachrichten aus der Chemie, 2013)

Suzuki cross-coupling in aqueous media - Hoffmann, Ina; Blumenröder, Bettina; Onodi, Silvia; Dommer, Sabine; Schatz, Jürgen (Green Chemistry, 2015)
We report a simple and efficient procedure for the ligand-free as well as ligand-assisted Suzuki reaction in both pure water and aqueous media. The cross-coupling reactions proceed successfully using phenylboronic acid or potassium phenyltrifluoroborate as a nucleophilic coupling partner. The method can be effectively applied to both activated and deactivated aryl halides yielding quantitative conversions. The catalytic activity of couplings performed in pure water increases when utilizing supramolecular additives, but decreases under standard phase-transfer conditions. Finally, the palladium loading is reducible from 3.0 mol% to 0.4 mol% without any loss of conversion.

Thiophene Metallation and Cross-Coupling Chemistry - Schatz, Jürgen; Hoffmann, Ina (2015)